Effectiveness of an Oral Health information, Education, and Communication Material on Knowledge, Attitudes, and Practices of Caregivers of Kindergarten Pupils in Aurora Quezon/Sittie Nor Rhizmin A. Tiang. - Tiang, Sittie Nor Rhizmin A., author
Objective. It has been recognized that the knowledge, attitudes, and practices (KAP) of the caregivers affect the children’s oral and general health. Prevention of oral diseases, like caries, can be achieved by giving an oral health education (OHE) to caregivers, specifically mothers. Health educators have agreed that they are an important target group for OHE being “key figures” that provide the greatest influence on their child’s life. This study intended to use and test the effectiveness of an Oral Health Information, Education, Communication (IEC) material which aimed to increase the caregivers’ oral health KAP that would lead to dental visits of the children, regardless if symptomatic or not.